Injectable Antimicrobial Conductive Hydrogels for Wound Disinfection and Infectious Wound Healing - Liang, Yongping; Chen, Baojun; Li, Meng; He, Jiahui; Yin, Zhanhai; Guo, Baolin (Biomacromolecules, 2020)
As the abuse of antibiotics continues to increase, the emergence of antibiotic resistance and unknown drug-resistant bacterial infections pose a great threat on people worldwide. In this work, we aimed to develop a series of injectable antimicrobial conductive hydrogels based on glycidyl methacrylate functionalized quaternized chitosan (QCSG), gelatin methacrylate (GM), and graphene oxide (GO) for drug-resistant bacterial disinfection and infectious wound healing. The rheology, morphology, mechanical properties, and electrical and photothermal properties of the hydrogels were characterized. Furthermore, the good in vitro and in vivo intrinsic antibacterial, photothermal antibacterial, and antibiotics released antibacterial properties of this multiantibacterial hydrogel were verified. The good biocompatibility of these hydrogels was also investigated by cytocompatibility, hemocompatibility, and histocompatibility tests. In the drug-resistant Methicillin-resistant Staphylococcus aureus (MRSA) infected mouse full-thickness defect model, the wound closure rate, the length of dermal tissue gap, number of blood vessels and hair follicles in hematoxylin-eosin (HE) staining, the amount of collagen in Masson staining, and the related cytokines for the expression of inflammation (interleukin-6, IL-6) and regeneration of blood vessels (vascular endothelial growth factor, VEGF) in immunofluorescence were all further studied. All the results demonstrated the better wound healing effect of these multiantibacterial injectable conductive hydrogel in infectious skin tissue defect repair, indicating their great potential for infected wound healing.